The Strategy of Improving the Performance of Cooperatives in the Review of Organizational Culture, Innovation is Mediated by the Entrepreneurial Orientation in Surabaya - Tri Andjarwati; Endah Budiarti; Beni Agus Setiono (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: The aim of research to proved and analyzed strategy to improve cooperative performance through organizational culture, innovation in mediation with entrepreneurship orientation in surabaya city.